Touch type working driving control device of hole digging and fertilizer injection mechanism - Li Mutong; Zhou Fujun; Li Xiaoli (2016)
The invention provides a touch type working driving control device of a hole digging and fertilizer injection mechanism and belongs to agricultural machinery. A frame body is fixedly provided with a motor and a force sensitive sensor; an electromagnetic clutch valve is mounted on a motor shaft of a motor; a lead wire is used for communicating the force sensitive sensor with the electromagnetic clutch valve; a touch needle rod is hinged and mounted on the frame body in a swinging manner; a slide block is assembled on the frame body and on the part between the touch needle rod and the force sensitive sensor; the two ends of a driving connection rod are hinged to the touch needle rod and the slide block respectively; the slide block and the force sensitive sensor are in contact matching or released contact matching; the two ends of a resetting tension spring are connected with the touch needle rod and the frame body respectively. The work control on a solid-state chemical fertilizer hole digging and injection fe